Mild to Moderate to Severe: What Drives the Severity of ARDS in Trauma Patients?. Issue 6 (June 2018) - Daher, Pamela; Teixeira, Pedro G.; Coopwood, Thomas B.; Brown, Lawrence H.; Ali, Sadia; Aydelotte, Jayson D.; Ford, Brent J.; Hensely, Adam S.; Brown, Carlos V.
Acute respiratory distress syndrome (ARDS) is a complex inflammatory process with multifactorial etiologies. Risk factors for its development have been extensively studied, but factors associated with worsening severity of disease, as defined by the Berlin criteria, are poorly understood. A retrospective chart and trauma registry review identified trauma patients in our surgical intensive care unit who developed ARDS, defined according to the Berlin definition, between 2010 and 2015. The primary outcome was development of mild, moderate, or severe ARDS. A logistic regression model identified risk factors associated with developing ARDS and with worsening severity of disease. Of 2704 total patients, 432 (16%) developed ARDS. Of those, 100 (23%) were categorized as mild, 176 (41%) as moderate, and 156 (36%) as severe. Two thousand two hundred and seventy-two patients who did not develop ARDS served as controls. Male gender, blunt trauma, severe head and chest injuries, and red blood cell as well as total blood product transfusions are independent risk factors associated with ARDS. Worsening severity of disease is associated with severe chest trauma and volume of plasma transfusion. Novel findings in our study include the association between plasma transfusions and specifically severe chest trauma with worsening severity of ARDS in trauma patients.